Searching for Dumbledore: A reflection upon the outcomes of a tailored emotional literacy programme on three key stage 2 children. Issue 2 (21st September 2018) - Kay, Lynda
Abstract : Some children may only be able to express feelings of anxiety, frustration, stress or sadness through angry behaviours, which may prove challenging for schools (Barnes et al ., 2016; Shechtman and Tutian, 2016). This is problematic when considered in relation to research evidence highlighting the negative impact such behaviours may have upon social relationships and academic outcomes (Sloan et al., 2017). The aims of this study were to explore whether a tailored emotional literacy programme can be used effectively to extend children's emotional lexicon and strategies for the self‐management of behaviours. Three children with social‐emotional difficulties were taught in twelve weekly sessions. The findings from this study suggests the positive benefits of using a programme tailored to meet a child's specific needs (rather than a programme without any adaptations), which may be an effectual tool in supporting children to change established patterns of negative behaviours.